Human rights and Chinese thought : a cross-cultural inquiry - Angle, Stephen C., 1964- (Cambridge modern China series., 2002)
"China poses great challenges to human rights in theory and practice. In practice, China is considered, by the measure of most Western countries, to have a patchy record of protecting individuals' human rights. In the theoretical realm, Chinese intellectuals and government officials have challenged the idea that the term "human rights" can be universally understood in one single way and have often opposed attempts by Western countries to impose international standards on Asian countries." "What should we make of these challenges - and of claims by members of other groups to have moralities of their own? Human Rights and Chinese Thought gives an extended answer to these questions in the first study of its kind. Stephen C. Angle integrates a full account of the development of Chinese rights discourse - reaching back to important, although neglected, origins of that discourse in seventeenth- and eighteenth-century Confucianism - with philosophical considerations of how various communities should respond to contemporary Chinese claims about the uniqueness of their human rights concepts." "Drawing on Western thinkers such as Richard Rorty, Alasdair MacIntyre, Michael Walzer, Allan Gibbard, and Robert Brandom, Angle elaborates a plausible kind of moral pluralism and demonstrates that Chinese ideas of human rights do indeed have distinctive characteristics. His conclusion is not that we should ignore one another, though. Despite our differences, Angle argues that cross-cultural moral engagement is legitimate and even morally required. International moral dialogue is a dynamic and complex process, and we all have good reasons for continuing to work toward bridging our differences."--Jacket